Study on reproduction of razor clam, Solen regularis Dunker, 1862 (Bivalvia : Solenidae in the western part of Sarawak, Malaysia - Aileen May, Ridis Rinyod (University Malaysia Sarawak, UNIMAS, 2012)
Razor clam or ‘ambal’ is a highly priced marine bivalve collected using traditional methods from several intertidal sandy beaches and mudflats by local people of Sarawak. ‘Ambal’ of Sarawak belongs to Family Solenidae with three different species namely i) Solen regularis Dunker, 1862, ii) S. lamarckii Chenu, 1843 and iii) S. sarawakensis von Cosel, 2002. In this study, the reproduction of S. regularis was monitored for a duration of two years (March 2007 until February 2009) at Asajaya Laut and Buntal, located in the western part of Sarawak. Samples were taken at a two-week interval or monthly with in-situ physico-chemical parameters of sea water (temperature, dissolved oxygen, pH and salinity) measurement and analysis of chlorophyll-a concentration in the water. This study has two main parts which were gonadal condition index (GCI) study and histological study on the gonad. The objectives of this study were to determine the reproductive cycle of S. regularis, to observe the possible effect of environmental factors on the clam’s reproduction and to elucidate the stages of gonadal development through drawing up a gametogenic scale using histological methods. GCI study was monitored for 24 months (March 2007 to February 2009) as an initial approach to sexual development through monitoring the reproductive cycle of the razor clam and to observe the effect of environmental factors towards the cycle. A maximum of 30 specimens were dissected from each sampling for sex identification and GCI. The male gonad appeared beige in colour while female gonad is whitish. Throughout the study, the mean GCI ranged from 0.000 to 0.247 (± 0.077) at Asajaya Laut and 0.000 to 0.253 (± 0.079) at Buntal. Based on the mean GCI pattern, the reproductive cycle for both study sites showed similar pattern with five stages as follows; i) gonadal development (during the increment of GCI value) ii) maturation (during the maxima GCI value), iii) spawning (indicated by the decreasing GCI value after the maxima), iv) spent (occurred after the last spawning which indicate the end of active phase of reproduction) and v) resting period (during the minima GCI value). Spawning period was observed from end of March-April to September and followed by a resting period from end of October to January in the following year. Throughout the study, there were slight differences in the timing of the reproductive cycle stages occurred at each site whereas only at Buntal that chlorophyll-a showed moderate correlation with the mean GCI (r = 0.513, p = 0.001). The gametogenic cycle was determined using histological methods together with GCI data. In Asajaya Laut, study was carried out starting from February 2008 until February 2009 while the study in Buntal started one month later. Results showed that the histological structures of males and females S. regularis gametes can be characterized into seven gametogenic cycle stages as follows; i) sexual rest (Stage 0), ii) start of gametogenesis (Stage I), iii) advance gametogenesis (Stage II), iv) ripe (Stage IIIA), v) spawning (Stage IIIB), vi) restoration (Stage IIIC) and vii) spent (Stage IV). The result of histological study validates the GCI findings. It was noted that during the maxima GCI value, majority of the individuals were in Stage III while during the minima GCI value, they were in their sexual rest (Stage 0). At both locations, S. regularis populations were in their Stage 0 from November to December and gametogenesis (Stage I) began in January. S. regularis showed prolonged spawning activity indicated by their active phase of reproduction (Stage IIIA, IIIB and IIIC) from February to September and January to October for Asajaya Laut and Buntal, respectively. High percentage of razor clam individuals entered their spent stage in October for both sites which complete the whole gametogenic cycle. However, towards the end of spawning period and early part of the gametogenesis, individuals collected within the same month did not show a uniform gametogenic cycle stage. Infestation of endoparasites in the gonadal cavity was also observed in S. regularis involving two types of endoparasites (nematodes and trematode). However, detail investigation was not carried. Therefore, study on the infections of those endoparasites is crucial in order to investigate the effect of the endoparasites infection to the razor clam reproduction and food safety status for human consumption. The outcomes of this study had provided valuable information on the reproduction of S. regularis. Findings from this can be used for the conservation purpose, establishment of sustainable razor clam fishery management and for future aquaculture in Sarawak. Keywords: Solen regularis, Gonadal Condition Index (GCI), histological, reproductive and gametogenic cycle, Asajaya Laut, Buntal.